2015
DOI: 10.1016/j.jocrd.2014.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of childhood obsessive–compulsive personality traits in adults with obsessive compulsive disorder versus obsessive compulsive personality disorder

Abstract: Identifying risk factors of psychopathology has been an important research challenge. Prior studies examining the impact of childhood temperament on adult disorder have largely focused on undercontrolled and inhibited presentations, with little study of overcontrolled traits such as obsessive-compulsive personality traits (OCPTs). We compared rates of childhood OCPTs in adults with OCD (without OCPD) (n = 28) to adults with OCPD (without OCD) (n = 27), adults with both OCD and OCPD (n = 28), and healthy contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…It is widely known that medications can affect the preferences of OCD subjects during the IGT task (Long et al, 2015). The co-existence of OCD and OCPD results in more severe impairments in terms of executive function when compared to OCD without OCPD (Pinto et al, 2015). Research should be continued in more patients who have only OCD or OCPD and are not taking medication.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely known that medications can affect the preferences of OCD subjects during the IGT task (Long et al, 2015). The co-existence of OCD and OCPD results in more severe impairments in terms of executive function when compared to OCD without OCPD (Pinto et al, 2015). Research should be continued in more patients who have only OCD or OCPD and are not taking medication.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, studies with adults have noted that OCPD is associated with greater contamination, symmetry, and doubting symptoms [4,7,13]. While these results are compelling, longitudinal studies are necessary to evaluate the trajectory of childhood OCPTs into adulthood and determine whether OCPTs may serve as a marker for OCD youth who are at risk of developing OCPD.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of adults with OCPD (with and without comorbid OCD) retrospectively reported higher rates of perfectionism, inflexibility and drive for order during childhood relative to healthy controls [13]. Other retrospective reports of OCPTs in childhood have also predicted the development of other psychiatric disorders, particularly within eating disorder samples [14].…”
Section: Introductionmentioning
confidence: 99%
“…Studies showed that there is a tendency to develop avoidance habits in OCD patients, providing support for a habit account of OCD (6). A number of studies found a relationship between obsessivecompulsive personality traits and behavioral inhibition (7,8).…”
Section: Introductionmentioning
confidence: 95%